(untitled) (Asian Journal of Pharmaceutics (AJP), 2025)
Aim: The current study aimed to develop orally dispersible tablets (ODTs) of ibuprofen using the direct compression method, incorporating modified agar (FD formulation) and an agar-effervescent mixture (FE formulation) as disintegrants. Materials & Methods: Formulations were prepared using the direct compression technique. Two types of disintegrants were employed: modified agar and agar-effervescent mixtures. The prepared tablets were evaluated for multiple quality control parameters including weight variation, uniformity of active pharmaceutical ingredient (API), wetting time, hardness, thickness, disintegration time, friability, hydration capacity, in vitro dispersion time, drug release profile, preliminary stability, and compatibility between API and excipients. FTIR spectroscopic analysis was performed to assess potential drug-excipient interactions. Drug release studies were conducted using phosphate buffer (pH 6.8), and release kinetics were analyzed using established mathematical models. Results & Discussion: The powder blends exhibited satisfactory flow and compressibility characteristics suitable for direct compression. All formulated tablets showed no signs of chipping, capping, or sticking during manufacturing. Tablet hardness, friability, and disintegration times were within pharmacopeial limits. Among the formulations, FD4 and FE3 demonstrated superior performance, with in vitro dispersion times of 44 seconds and 49 seconds, respectively, and wetting times of less than one minute. Both formulations exhibited high drug release-97.17% (FD4) and 98.29% (FE3)-within 15 minutes, following firstorder release kinetics and the Higuchi diffusion model. FTIR analysis confirmed no drug–excipient incompatibility. Short-term stability studies indicated no significant changes in dispersion time or drug content, and statistical analysis supported the stability of both formulations. These results indicate that both FD4 and FE3 are promising candidates for fast-dissolving ibuprofen tablets. Conclusion: This study successfully formulated orally dispersible tablets of ibuprofen using a simple and cost-effective direct compression method. The developed tablets disintegrated rapidly in the oral cavity, showed good mechanical strength, and achieved enhanced drug dissolution. The promising performance of FD4 and FE3 formulations suggests that ODTs of ibuprofen containing superdisintegrants could be effective in managing conditions like emesis, offering rapid onset of action without the need for water.